A new species of Rudgea (Palicoureeae, Rubiaceae) from Espírito Santo state, Brazil - Torres-Leite, Filipe; Bruniera, Carla P.; Zappi, Daniela C.; Carrijo, Tatiana T. (Phytotaxa, 2018)
A new endemic and critically endangered species of Rudgea (Rubiaceae) from Southeastern Brazil is described and illustrated. Rudgea minutifolia Bruniera & Torres-Leite is distinguished by its small leaves, a character found in only a handful of species in this genus. The indumentum of the branches, leaves and stipules, low number of secondary veins, corniculate corolla lobes, and vinaceous to almost black mature fruits are also characteristic of this species. Discovered in a forest remnant within the Atlantic Rainforest domain in the south of Espírito Santo state, this species is found only in the municipality of Castelo, an area that has been recognized as prioritary for conservation. Besides the description, taxonomic comments, conservation status, images and illustrations are provided.